Interference Requirements of Type Iii Crispr-Cas Systems from Thermus Thermophilus - Ispolatov, y (Academic Press, 2024)
Among the diverse prokaryotic adaptive immunity mechanisms, the Type III CRISPR-Cas systems are the most complex. The multisubunit Type III effectors recognize RNA targets complementary to CRISPR RNAs (crRNAs). Target recognition causes synthesis of cyclic oligoadenylates that activate downstream auxiliary effectors, which affect cell physiology in complex and poorly understood ways. Here, we studied the ability of III-A and III-B CRISPR-Cas subtypes from Thermus thermophilus to interfere with plasmid transformation. We find that for both systems, requirements for crRNA-target complementarity sufficient for interference depend on the target transcript abundance, with more abundant targets requiring shorter complementarity segments. This result and thermodynamic calculations indicate that Type III effectors bind their targets in a simple bimolecular reaction with more extensive crRNA-target base pairing compensating for lower target abundance. Since the targeted RNA used in our work is non-essential for either the host or the plasmid, the results also establish that a certain number of target-bound effector complexes must be present in the cell to interfere with plasmid establishment. For the more active III-A system, we determine the minimal length of RNA-duplex sufficient for interference and show that the position of this minimal duplex can vary within the effector. Finally, we show that the III-A immunity is dependent on the HD nuclease domain of the Cas10 subunit. Since this domain is absent from the III-B system the result implies that the T. thermophilus III-B system must elicit a more efficient cyclic oligoadenylate-dependent response to provide the immunity. © 2024